Design of a kite controller for airborne wind energy - Milandri, Matteo (Department of Electrical Engineering, 2015)
Airborne wind energy is a field of technology being developed to make use of the vast, renewable wind power resource which is above the reach of traditional wind turbines, without the need for a large tower. Much analytical research has been undertaken in recent years to better understand the problem space. However, there are relatively few working systems that demonstrate their functioning and can be compared with simulations and theory. Off-grid power systems still rely heavily on diesel generators, so devices that tap renewable energy sources with similar ease of deployment and lower cost of energy would help this sector to reduce its reliance on expensive, polluting, fossil fuels. The development of these systems is often performed by teams with business interests leaving little open access content available regarding the design process of such devices or the data that they provide. A kite control pod has been designed for the remote control of a standard kitesurfing kite and a prototype has been demonstrated stably flying such a kite on a fixed length tether. This pod and kite would be tethered to a winch and as the kite flies across the wind, the lift force generated is applied to the winch which is reeled out and electrical power generated. Once fully extended, the tether would be reeled in with the kite de-powered, using some of the generated energy, stored in a battery. This system can then be used as a test bed for the further development of a compact, autonomous, airborne wind energy system for off-grid applications.